Determination of Specific and Non-Specific Parameters of Ethanol Extract of Propolis from Tetragonula sp. - Maulira, Dinda Ayu; Suhayatman, Early Windari; Ridwan, Sucilawaty; Wahyuni, Nurul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Propolis, which is produced by Tetragonula sp., has the potential to treat a number of illnesses, including microbial infections, wounds, depression, and cancer. However, in order for propolis to be used as a raw material for traditional medicine, it must be standardized. The goal of this study was to standardize the values of specific and non-specific parameters. Propolis was extracted using the maceration method with 70% ethanol solvent until a thick extract was obtained, and the thick extract was tested for both specific and non-specific parameters. In terms of specific parameters, the obtained extract is a thick yellowish-brown liquid, has a characteristic sour propolis scent, and is sticky. Phytochemical screening also showed that the extract was positive for flavonoids, phenolics, alkaloids, saponins and tannins. Meanwhile, the nonspecific test obtained a drying shrinkage value of 35.059%, moisture content of 33.698%, specific gravity of 1.0082 g/ml, and total ash content of 1.26%. The results of the specific and nonspecific parameter tests have met the established extract requirements. Further quantitative identification of the activity of compounds in propolis is recommended for the development of traditional medicine.